dataDryadPCR - Legagneux, Pierre; Berzins, Lisha L.; Forbes, Mark; Harms, Naomi Jane; Hennin, Holly L.; Gilchrist, H. G.; Bourgeon, Sophie; Bêty, Joël; Soos, Catherine; Love, Oliver P.; Foster, Jeffrey T.; Descamps, Sébastien; et al. (Dryad Digital Repository, 2014)
Data with information on the carrier status of Pasteurella multocida labelled "PCR CARRIER STATUS" and several immune traits of Common eiders